2012
DOI: 10.2215/cjn.04100412
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Strategies to Increase Organ Donation

Abstract: Summary Background and objective The acceptability of financial incentives for organ donation is contentious. This study sought to determine (1) the acceptability of expense reimbursement or financial incentives by the general public, health professionals involved with organ donation and transplantation, and those with or affected by kidney disease and (2) for the public, whether financial incentives would alter their willingness to consider donation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Legislative authorization to expand the NLDAC to include reimbursement of lost wages (with an appropriate cap) and other direct expenses as well as the removal of financial means testing is an immediate priority to reduce the effects of class and racial disparities. Transplant patients, living donors, the general public, community nephrologists, and transplant providers all strongly support reimbursement of donation-related expenses to achieve financial neutrality for living donors (36,(71)(72)(73), and at least 17 countries have launched pilot or national programs that include reimbursement for living donor lost wages (74).…”
Section: Recommendation 1: Remove Financial Disincentives To Lkdmentioning
confidence: 99%
“…Legislative authorization to expand the NLDAC to include reimbursement of lost wages (with an appropriate cap) and other direct expenses as well as the removal of financial means testing is an immediate priority to reduce the effects of class and racial disparities. Transplant patients, living donors, the general public, community nephrologists, and transplant providers all strongly support reimbursement of donation-related expenses to achieve financial neutrality for living donors (36,(71)(72)(73), and at least 17 countries have launched pilot or national programs that include reimbursement for living donor lost wages (74).…”
Section: Recommendation 1: Remove Financial Disincentives To Lkdmentioning
confidence: 99%
“…Living donors would still be able to donate to a relative/friend or anonymously to the waiting list, and all living donors would receive payment. In the absence of data from high-quality studies examining the impact of financial incentives on living kidney donation rates, our estimates were based on a recent survey (10), which found that, of those who would not consider donating at baseline, 54% would consider donating to a relative for payment of $10,000 from a third party government payer on donation. Because this survey only measured intent to consider donation, we used a conservative estimate of an increase of 5% in transplants-representing five additional paid living donors in a 100 total transplant/yr program-if $10,000 were offered through a paid living donor strategy to all living donors in the base case analysis and considered a broad range of estimates in sensitivity analyses.…”
Section: Interventionmentioning
confidence: 99%
“…Multiple strategies to increase living donation have been proposed, including limiting financial disincentives for living donors (6)(7)(8)(9). Recently, we conducted a survey examining the acceptability of financial incentives to increase the number of kidneys for transplantation (10). Most respondents reported that financial incentives were an acceptable strategy to increase the number of living donor kidneys for transplantation, and nearly one half found monetary payment an acceptable form of financial incentive.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies in North America have examined the attitudes of potential donors (17), and others (18) on the effect of financial compensation on willingness to donate, a (crowding out) disincentive to donate, and/or whether a quantifiable limit can be generalized, after which an offer becomes an undue inducement. Halpern et al (19) used conjoint analysis in which participants assessed their own willingness to donate when conditions such as risk levels were experimentally changed in hypothetical scenarios.…”
Section: Introductionmentioning
confidence: 99%